Corrosion behavior and analysis on friction stir welded aluminium matrix composites. (1st June 2022) - Selvamani, S T; Bakkiyaraj, M; Palani, S; Yoganandan, G
Abstract: Friction stir welded (FSW) AA6061 aluminium matrix composites (AMCs) joints with 10% SiC particles were taken under investigation to reduce the corrosion rate. This study integrates the response surface methodology to optimize process parameters of FSW to achieve defect-free AMCs joints. The joint strength of 252 MPa was estimated as maximum tensile strength under rotational speed of 900.38 rpm and thrust force of 20.48 MPa. Furthermore, the turbulence flow of plasticized materials contributes to the restructuring of grains in the weld zone, and it is mainly influenced by the tool rotation. The cyclic potentiodynamic polarization test has been carried out in the different zones of friction stir welded AMCs joints using a 3.5% sodium chloride (NaCl) solution that is aerated naturally at 25 °C. It was seen that the corrosion polarization value of the Heat affected zone (HAZ) is 400 μ A cm 2, the un-welded aluminium matrix composite is 345 μ A cm 2, and the stir zone is 751 μ A cm 2 at the optimized conditions. The corrosion study reveals that the SiC reinforcement was a suspicious agent that propagated the pits in larger and deeper sizes when the various zones of the welded joint were exposed to electrochemical studies.